A Quantitative Study of the Strategic Arms Race in the Missile Age - McGuire, Martin (The Review of Economics and Statistics, 1977)
For many years, public officials and analysts have been acutely aware of a fundamental interaction between Soviet and U.S. decisions on nuclear forces. The force level, technology, and mix that each side considers adequate for its own security depends on the existing (or anticipated) force level, technology, and mix of its adversary. Various models (see Brubaker, 1972; Brito, 1972; Intriligator, 1975; McGuire, 1965, 1967)-some predating the cold war altogether-have been proposed to deduce the implications of mutual interdependence, so as to understand the nature of this Arms Race process. While numerous theoretical explanations exist, the opportunity for testing out the alternate models is necessarily restricted, in that one must wait for sufficient historical data to accumulate. In view of the fact that 15 years of historical data since the introduction of intercontinental missiles in 1960 are now available in an unclassified form,' certain empirical tests to explore the nature of the arms race and of interaction between the United States and the U.S.S.R. appear feasible and desirable. This paper reports on data collection, model formulation, and preliminary regression analysis into this problem. Since rather more subtle formulations and substantially more exhaustive regression runs are required to produce definitive results, the conclusions reached so far must be qualified as tentative. The first purpose of the study is to analyze the historical data, so as (1) to discern whether an interaction process gave rise to the data; (2) to describe the process in quantitative terms to include the stability of Soviet and American behavior and points of equilibrium in their mutual competition; and (3) in some degree to predict its future course. Because of its inherent intuitive appeal and its correspondence with casually observed force-structure decisions in the U.S. context, there is a strong presumption that some such interaction exists. Therefore, another objective of the study is to compare alternative measures of strategic strength to see which measure yields the best, most intuitively plausible quantitative description of this interaction process, on the prior assumption that such a process exists.